The stories of supervision: creative writing in a critical space - Berry, Marsha; Batty, Craig (New writing (Clevedon, England), 2016)
Supervising PhD candidates is a story in itself. Like a novel or screenplay, there are protagonists and antagonists, emotional transformations, dramatic twists and turns, and nearly always rising tension - especially in the domain of creative practice, where methodologies and research artefacts are still debated and contested. Voiceover narration comes into play, too, from both the candidate ('Does my supervisor know what I'm trying to do?') and the supervisor ('Does my candidate really think this is research?'). And hopefully there is always a happy ending - or at least happy subject to minor revisions. There is a growing body of literature about PhD supervision. Here we seek to expand on this work by drawing specific attention to the supervision of the Creative Writing PhD in the contemporary academy in the Australian and British contexts, and in a form that befits this vibrant research discipline. In this paper, then, we make connections between theory and practice by presenting a series of fictionalised vignettes drawn from our collective experiences of supervising candidates. By being playful ourselves, we offer a creative-critical exploration of the creative practice research space that illuminates some of the challenges and opportunities for supervising in the discipline.